Feasibility of using regional sentinel surveillance to monitor the rotavirus vaccine impact, effectiveness and intussusception incidence in the African Region. Issue 13 (23rd March 2017) - Mandomando, Inácio; Weldegebriel, Goitom; de Deus, Nilsa; Mwenda, Jason M.
Abstract: The 9th African rotavirus symposium was held in Maputo, Mozambique from the 8th to 10th of December 2015, including a total of 101 delegates from 17 countries, 15 of which were African countries. This forum brought together participants with various expertise including scientists, clinicians, immunization program managers, public health officials and policymakers. By the time of the symposium, 29/47 (61%) of countries in the World Health Organization (WHO) African Region had introduced rotavirus vaccine into their routine immunization program. Countries that had started monitoring impact and effectiveness of the rotavirus vaccines as well as potential adverse events following immunization (AEFI) including intussusception) also participated. Seven Rotarix® vaccine-using countries and another four countries that are using the Rotateq® vaccine are conducting systematic surveillance on intussusception and report data to the WHO and partners. The symposium concluded that the regional rotavirus surveillance network has played a crucial role in pre-vaccine data through documenting burden and epidemiology of rotavirus diarrhea in Africa, seasonal trends and identifying common rotavirus genotypes. The sentinel surveillance platform is now being used to assess the impact of the vaccines and monitoring adverse events with a focus on intussusception.